1998
DOI: 10.1007/s004240050530
|View full text |Cite
|
Sign up to set email alerts
|

Circadian changes in the sweating-to-vasoconstriction interthreshold range

Abstract: Thermoregulatory defenses are characterized by thresholds, the core temperatures triggering each response. Core body temperature is normally maintained within the interthreshold range, temperatures between the sweating and vasoconstriction thresholds that do not trigger autonomic defenses. This range usually spans only some 0.2 degrees C, but it remains unknown whether similar precision is maintained during the circadian core temperature cycle of about 0.8 degrees C. Accordingly, we evaluated the interthreshol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 31 publications
7
43
0
1
Order By: Relevance
“…Average core temperatures with passive insulation and either active warming system differed by £ 0.5°C at the end of the pre-CPB period and on arrival in the ICU. Such small temperature differences are not usually considered to be clinically important as they have yet to be linked to any important outcome [18]; furthermore, normal circadian temperature change exceeds 0.5°C and is presumably harmless [19,20]. Therefore, neither active underbody system made a clinically important contribution to thermal management in patients managed in this manner.…”
Section: Discussionmentioning
confidence: 99%
“…Average core temperatures with passive insulation and either active warming system differed by £ 0.5°C at the end of the pre-CPB period and on arrival in the ICU. Such small temperature differences are not usually considered to be clinically important as they have yet to be linked to any important outcome [18]; furthermore, normal circadian temperature change exceeds 0.5°C and is presumably harmless [19,20]. Therefore, neither active underbody system made a clinically important contribution to thermal management in patients managed in this manner.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is consistent with those reported from the only other investigation of circadian variations in thermoregulatory effector responses to cooling (103). Tayefeh et al (103) observed no difference in the cooling-induced vasoconstriction threshold between 0700 h and 1600 h, although a shift was apparent by 0300 h. However it is unclear to what extent that shift resulted from sleep deprivation as opposed to circadian rhythm effects (103). We…”
Section: Resultsmentioning
confidence: 59%
“…[14][15][16] These limits reflect the normal magnitude of human circadian temperature variation. 17,18 We performed a Bland-Altman analysis to evaluate agreement between the temperature measurement methods, assuming that the true value changes from measurement to measurement. 13 In a Bland-Altman analysis, the bias and 95% limits of agreement are determined.…”
Section: Discussionmentioning
confidence: 99%